ODTMA+ and HDTMA+ organo-montmorillonites characterization: New insight byWAXS, SAXS and surface charge - Bianchi, Ana Elisa (2013)
In this work we investigate the microstructure and properties of organo-montmorillonites (OMts) synthesized by intercalation of a Patagonian Mt with different surfactant/CEC ratios (0.5, 1 and 2) of octadecyl trimethylammonium (ODTMA+) and hexadecyl trimethylammonium (HDTMA+) cations. X-ray diffraction (XRD) patterns showed that in all OMt samples d001 value increases with respect to raw Mt (1.258 nm). Small angle andwide angle X-ray scattering (SAXS andWAXS) curves, particle apparent diameters (determined by laser), zeta potential values and scanning electron microscopy (SEM) images, showed the presence of assorted d001 values (which depend on storage conditions), aggregate formation and charge reversal (which varied with loading and cation length) for samples obtained with 1 and 2 CEC. However, for samples intercalatedwith 0.5 CEC, we found evidence of smaller aggregate formation, no charge reversal, and similar d001 and zeta potential values (both higher than those of Mt). Findings reported here will help attain better conditions to functionalize highly charged Mt making them suitable to be used as nanocomposite precursors for different applications.